Pengaruh Social Media Marketing Terhadap Brand Equity, Brand Trust, Dan Brand Loyalty Pada Instagram Traveloka - Tarisa; Giri, Refi Rifaldi Windya (eProceedings of Management, 2024)
This research is entitled “The Effect of Social Media Marketing on Brand Equity, Brand Trust, and Brand Loyalty on Traveloka Instagram”.on Traveloka Instagram”. The main focus is to understand the influence of social media marketing activities onbrand trust, brand equity, and brand loyalty on Traveloka's Instagram platform. The background of this research is based onthe tourism industry in Indonesia is growing rapidly along with the widespread use of social media that affects marketing methods.which affects marketing methods. The phenomena in this study were explored using a questionnaire survey method using a Likert scale.questionnaire survey method that uses a Likert scale with the criteria of Instagram social media users and the Traveloka application in the DKI Jakarta area and analysis of social media users.Traveloka in the DKI Jakarta area and SEM-PLS analysis. The purpose of this study is to identify the influence ofsocial media marketing on Traveloka's brand trust, brand equity, and brand loyalty on Instagram. This is importantconsidering the growth of Indonesia's tourism sector and the important role of social media in online marketing strategies.travel agents (OTA) marketing strategy. The results showed that social media marketing has a significant influence on brand equity, brand trust, and brand loyalty.on brand equity, brand trust, and brand loyalty. In addition, the factor that needs to be considered is brand trust because it has the greatest influence than other variables, indicating that trust is the most important.because it has the greatest influence than other variables, which indicates that consumers' trust in the brand affects their perceived value and their desire to remain loyal to the brand.consumers' trust in the brand affects their perception of value and their desire to remain loyal to the brand.brand. The benefits of this research include theoretical contributions in the field of management, especially in the aspects of social media marketing, brand trust, brand equity, and brand equity.media marketing, brand trust, brand equity, and brand loyalty, as well as practical benefits for academics and companies in planning marketing strategies and business development.in planning marketing strategies and business development. Keywords-social media marketing, brand trust, brand equity, brand loyalty, online travel agents.